Herbal medicine use and renal dysfunction among persons living with HIV on Tenofovir-based ART in Kampala, Uganda - Stuart Niwagaba; Anthony Muyunga; Douglas Bulafu; Joslyline Lydia Nakanwagi; Sandra Lunkuse; Faizo Kiberu; Shivan Nuwasiima; Elizabeth Nagawa; Irene Karungi; Vella Ayugi; Patience Muwanguzi; Henry Kyeyune; et al. (PLoS ONE, 2026)
Introduction HIV/AIDS remains a major public health issue, with about 1.4 million people infected in Uganda by 2020. In rural western Uganda, 57.6% of people living with HIV (PLWH) use herbal medicine (HM) alongside antiretroviral therapy (ART). Combining HM with a tenofovir disoproxil fumarate (TDF)-based ART regimen may increase risks of renal dysfunction, death, and treatment costs, highlighting the need to study their combined effects. Objective To determine the prevalence of herbal medicine use and its association with renal dysfunction among patients on tenofovir antiretroviral treatment-based regimen at ISS clinic Mulago. Methods A cross-sectional study at MJAP ISS-clinic involved 414 HIV/AIDS patients on TDF-based ART from March–May 2023. Data on herbal medicine use and ART regimen were collected via interviews; blood samples were taken for renal function. Additional clinical and demographic data were extracted from records. All data were entered into Epidata and analyzed using STATA version 17. Results We enrolled 414 participants with median age (interquartile range) of 36 (30,44) years, majority were female 290 (70.1) and were on firstline regimen 392 (94.7). The prevalence of herbal medicine use was 70.8% (95% CI 66.2–74.9). The commonly used herbal medicines reported were concoction/crude, medicated clay and powdered products. The overall renal dysfunction prevalence was 22.5% (95 CI 18.7–26.8) The median serum creatinine levels among herbal medicine users was 96 µmol/litre and 88.8 µmol/litre among non-users. There was a significant difference in the median serum creatinine in the two groups (P = 0.028). There was no significant difference in the urea levels in the two groups (2.99 mmol/litre in herbal medicine users versus 2.84 mmol/litre in non-users, P = 0.689). Herbal medicine use was significantly associated with renal dysfunction (aPR-2.31, 95% CI 1.35–3.97). Other factors that were associated with renal dysfunction were age (aPR-1.54, 95% CI 1.08–2.22) sex (aPR-0.52, 95% CI 0.33–0.83), hypertension (aPR-3.43, 95% CI 2.47–4.76) and diabetes (aPR-1.79, 95% CI 1.39–2.31). Conclusion Health care workers should screen for herbal medicine use among ART patients and regularly monitor their renal function to detect dysfunction. The Ministry of Health and health care workers should also emphasize educating patients about the potential risks of combining herbal medicine with ART.